2021
DOI: 10.1021/acsmedchemlett.0c00611
|View full text |Cite
|
Sign up to set email alerts
|

Positional Isomers of Biphenyl Antimicrobial Peptidomimetic Amphiphiles

Abstract: Small-molecule antimicrobial peptidomimetic amphiphiles represent a promising class of novel antimicrobials with the potential for widespread therapeutic application. To investigate the role of spatial positioning for key hydrophobic and hydrophilic groups on the antimicrobial efficacy and selectivity, positional isomers of the lead biphenyl antimicrobial peptidomimetic compound 1 were synthesized and subjected to microbial growth inhibition and mammalian toxicity assays. Positional isomer 4 exhibited 4–8× inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Related structural amphiphiles have been identified as antimicrobial peptide mimics. 12,19,20 Compound 9 is a demonstrative example of how 6c can be used in a medicinal chemistry project. This bis-acylguanidine was found to be moderately active in a broth microdilution assay with a minimum inhibitory concentration (MIC) of 16 μg mL −1 against a range of Gram-positive clinical isolates including methicillin resistant Staphylococcus aureus , and vancomycin resistant S. aureus (MRSA, VRSA respectively), and multidrug resistant Streptococcus pneumoniae (see ESI,† Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Related structural amphiphiles have been identified as antimicrobial peptide mimics. 12,19,20 Compound 9 is a demonstrative example of how 6c can be used in a medicinal chemistry project. This bis-acylguanidine was found to be moderately active in a broth microdilution assay with a minimum inhibitory concentration (MIC) of 16 μg mL −1 against a range of Gram-positive clinical isolates including methicillin resistant Staphylococcus aureus , and vancomycin resistant S. aureus (MRSA, VRSA respectively), and multidrug resistant Streptococcus pneumoniae (see ESI,† Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Naphthyltriazole 40 was selected for an in vivo murine model trials of CDI but exhibited only mild evidence of in vivo efficacy indicating that further investigation into the structural and biological parameters affecting the in vivo efficacy of these antibacterial peptidomimetics is required, as the observed in vitro efficacy did not translate directly into in vivo efficacy. We have already reported that a correlation exists between increased hemolytic activity and an increase in hydrophobic/cationic ratio [ 15 ]; unfortunately, compound 40 exhibited a slight increase in hemolytic activity relative to the majority of tested compounds in this class with an HC 50 value of 32 µg/mL. While the selectivity ratio could be more substantial, this is acceptable for the future development of these gastrointestinal focused compounds.…”
Section: Discussionmentioning
confidence: 97%
“…There are many potential chemotherapeutics undergoing clinical trials for the treatment of CDI [ 12 ]. Other small molecule chemotherapeutics currently under investigation for use against C. difficile , include antimicrobial peptidomimetics [ 13 , 14 , 15 ], glycopeptides [ 16 ], bis-indoles [ 17 ], purine derivatives [ 18 ], tetramic acids [ 19 ], nitroheterocycles [ 20 ], macrolides [ 21 ], and nylon-3 polymers [ 22 ]. Two vaccines are being investigated in clinical trials (Pfizer and Intercell [ 23 ]), whereas bezlotoxumab (a monoclonal antibody targeting C. difficile TcdB) was given FDA approval in 2016 as adjunctive therapy for patients undergoing antimicrobial treatment who were at high risk of recurrent infection [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…9d), and among these isomers, the 4,4′-isomer (compound 36) showed potent antifungal activity against C. albicans with a MIC 80 of 1 μg mL −1 . 174 Apart from AMP mimicking small molecules, ionic liquids also possess promising antifungal therapeutic potential. Inspired by previously reported quaternary ammonium-based surfactants (QACs), Garcia et al designed and synthesized two series of cationic liquids by employing N-methylimidazole and pyridine as the core scaffold, and tethered different alkyl chains, including C 6 to C 14 , through a cleavable ester linkage (Fig.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%